IMPLEMENTASI PEMODELAN MATEMATIKA MENGGUNAKAN ALGORITMA GENETIKA DALAM MENYELESAIKAN PERMASALAHAN PENJADWALAN PROYEK KONSTRUKSI BANGUNAN - LUTFAN ANAS ZAHIR; KRISNA ACHMAD SUHUDI (PROGRAM STUDI TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS TULUNGAGUNG, 2023)
ABSTRACT The development of digitalization has accelerated since the covid-19 pandemic that hit the world in 2019.The role of digitalization in the economy is increasingly important, and is one of the enabling factors to increaseeconomic competitiveness in a country. Indonesia realizes the importance of digitalization for a country so that ithas initiated the mainstreaming of digital transformation and the implementation of the Strategic Priority Project(Major Project)